Caracterização da carne de avestruz (Struthio camelus) e desenvolvimento de embutido emulsificado defumado (mortadela) - Carvalho Filho, Edvaldo Vasconcelos de (2011)
Brazil is a developing country in which a significant proportion of the population has limited access to fresh meat, and as a substitutive for this item the alternative is the consume of meat derivated products, so it is high the consumption of products such as sausages and mortadella in Brazil. The aim of this study was to analyze the performance of ostrich meat from the deboned leg, the physical and chemical characteristics and the development and evaluation of smoked sausage from this meat. It was done the proximate composition, instrumental color, pH, water activity (aw), the instrumental texture, emulsification capacity and water absorption capacity of ostrich meat. For the development of smoked mortadella with modified starch and soybean oil was used a complete23 factorial design with 3 central points. It was assessed the stability of the emulsion, microbiological characteristics, proximate composition, instrumental color, pH, water activity (wa), the instrumental texture, capacity to retain water, the juice released from the packaging, weight loss from cooking and sensory evaluation of mortadella. Ostrich meat had presented excellent performance after deboned (87.27%), good percentage of macronutrients, highlighting the low amount of fat, good absorption capacity of oil and water. The mortadella presented a humidity varying from 71,56±0,72 to 68,17±0,52, lipids 10,86±0,31% to 15,84±1,11%, RMF 1,56±0,19% to 1,01±0,02%, protein from 15,23±0,73% to 12,40±0,49% and carbohydrates from 2,36±1,34% to 1,30±0,08%, instrumental texture of 0,13±0,01 the 0,29±0,05 Kgf/cm2, instrumental color for the parameter L * 52,83±0,42 to 60,96±0,58, the * 8,60±0,13 to 12,29±0,28, b * 11,36±0,04 to 13,84±0,16, stability of the emulsion from 48±0,43% to 86,61±0,79%, juice released from the packaging from 4,23±0,20% to 7,47±0,84%, weight loss from cooking from 1,40±0,24% to 10,92±0,00%, capacity of retention of water varied of 0,27±0,02% the 0,37±0,09%, pH in the rate from 6,29±0,00 to 6,52±0,03, 0,97±0,00 water activity of 0,98±0,00, and a good sensorial acceptance and purchase intention. It was possible to observe in this experiment that is feasible the elaboration of sausages with ostrich meat, with modified starch, soy oil and liquid smoking, maintaining the nutritional and technological qualities, which demonstrates the viability of its production.